2018
DOI: 10.1016/j.jacc.2018.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Remnant-Like Particle Cholesterol, Low-Density Lipoprotein Triglycerides, and Incident Cardiovascular Disease

Abstract: RLP-C and LDL-TG levels were predictive of CVD and associated with APOE variants. LDL-TG may represent a marker of dysfunctional remnant lipoprotein metabolism associated with increased CVD risk. Further research is needed to determine whether LDL-TG plays a causal role in CVD and may be a target for therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 51 publications
(52 reference statements)
7
92
0
1
Order By: Relevance
“…Diabetic dyslipidaemia is characterized by hypertriglyceridaemia and accumulation of remnant particles, and apoC‐III may aggravate the hypertriglyceridaemia by impairing the lipolysis of triglyceride‐rich lipoproteins. In addition, our results indicate that apoC‐III also affects the removal of remnant particles, resulting in an accumulation of atherogenic remnant particles . This may explain the improved postprandial lipemia and robust reduction of surrogate markers of remnant particles during liraglutide therapy.…”
Section: Discussionmentioning
confidence: 64%
“…Diabetic dyslipidaemia is characterized by hypertriglyceridaemia and accumulation of remnant particles, and apoC‐III may aggravate the hypertriglyceridaemia by impairing the lipolysis of triglyceride‐rich lipoproteins. In addition, our results indicate that apoC‐III also affects the removal of remnant particles, resulting in an accumulation of atherogenic remnant particles . This may explain the improved postprandial lipemia and robust reduction of surrogate markers of remnant particles during liraglutide therapy.…”
Section: Discussionmentioning
confidence: 64%
“…These authors have concluded that LDL-TG may represent a marker of dysfunctional remnant lipoprotein metabolism associated with increased CVD risk. 62) …”
Section: Why Are Elevated Triglyceride-rich Lipoproteins a Risk Factomentioning
confidence: 99%
“…sdLDL-C is a distinct LDL-C subclass, which is associated with raised TG and decreased HDL-C levels in adiposity and diabetes, playing a distinct metabolic role in atherosclerosis [15][16][17][18]. In this study including patients with T2DM, we found that there was an independent association between sdLDL-C and CHD.…”
Section: Discussionmentioning
confidence: 49%